Immunologic and vascular biomarkers of mortality in critical COVID-19 in a South African cohort - Shaw, Jane Alexandra; Meiring, Maynard; Snyders, Candice; Everson, Frans; Sigwadhi, Lovemore Nyasha; Ngah, Veranyay; Tromp, Gerard; Allwood, Brian; Koegelenberg, Coenraad F. N.; Irusen, Elvis M.; Lalla, Usha; Baines, Nicola; et al. (Frontiers in Immunology, 2023)
Biomarkers predicting mortality among critical Coronavirus disease 2019 (COVID-19) patients provide insight into the underlying pathophysiology of fatal disease and assist with triaging of cases in overburdened settings. However, data describing these biomarkers in Sub-Saharan African populations are sparse. We collected serum samples and corresponding clinical data from 87 patients with critical COVID-19 on day 1 of admission to the intensive care unit (ICU) of a tertiary hospital in Cape Town, South Africa, during the second wave of the COVID-19 pandemic. A second sample from the same patients was collected on day 7 of ICU admission. Patients were followed up until in-hospital death or hospital discharge. A custom-designed 52 biomarker panel was performed on the Luminex® platform. Data were analyzed for any association between biomarkers and mortality based on pre-determined functional groups, and individual analytes. Of 87 patients, 55 (63.2%) died and 32 (36.8%) survived. We found a dysregulated cytokine response in patients who died, with elevated levels of type-1 and type-2 cytokines, chemokines, and acute phase reactants, as well as reduced levels of regulatory T cell cytokines. Elevated IL-15 and IL-18 in those who died, and reducing levels over time in those who survived, suggest that fatal COVID-19 involved excessive activation of cytotoxic cells and the NLRP3 inflammasome. Elevated PCT, CRP, Endothelin-1, and VCAM-1 suggest that possible superinfection and endothelial dysfunction with thrombosis might have contributed to death. HIV infection did not affect the outcome. A clinically relevant biosignature including PCT, pH and lymphocyte percentage on differential count, had an 84.8% sensitivity for mortality, and outperformed the Luminex-derived biosignature.